Duodenal gastrointestinal stromal tumor and endoscopic ultrasound. - Castro-Poças, FM (2015)
Duodenal gastrointestinal stromal tumors (GISTs) are a very rare condition. The pre-operative diagnosis can be a challenge but it is very important because GISTs have singularities that differ from other tumors and their location in the duodenum itself can have a major role in the choice of the surgical approach. We present two cases of duodenal GISTs where endoscopic ultrasound had a single role in their management, namely allowing the possibility to obtain material for immunocytochemical pre-operative diagnosis and regarding the precise relation to the papilla of Vater. The patients were operated and histological examination confirmed the diagnosis in both cases.